Tissue expander breast reconstruction outcomes following postmastectomy radiation therapy in the era of neoadjuvant chemotherapy - Padilla, Oscar; Jairam, Meghan; Yen, Amanda; Choi, Julie; Buss, Elizabeth; Chin, Christine; Katz, Leah; Ascherman, Jeffery; Connolly, Eileen P. (Frontiers in Oncology, 2025)
BackgroundOptimal sequencing of mastectomy, tissue expander breast reconstruction (TE-BR), chemotherapy, and post-mastectomy radiotherapy (PMRT) remains unclear. While PMRT is known to impact TE-BR outcomes, limited data exist comparing outcomes between patients who also receive neoadjuvant chemotherapy (NAC) versus adjuvant chemotherapy (AC).MethodsA retrospective review of 126 patients diagnosed with invasive breast carcinoma who underwent mastectomy, TE-BR, and PMRT between 2001 and 2017 was conducted. Patients were stratified into NAC (n=74) and AC (n=52) cohorts. Logistic regression and Kaplan-Meier analyses evaluated TE-BR failure rates, completion rates, and radiation toxicity. Multivariate Cox proportional hazard regression modeled TE-BR failure probability.ResultsTE-BR failure rates were significantly higher in the NAC group (44.6% at a median of 18.7 months) compared to the AC group (26.9% at 23.2 months, p=0.041). Moreover, NAC was associated with increased adverse events and lower TE-BR completion rates (both p=0.001). Univariate analysis identified NAC (p=0.007) and acute RT toxicity (p<0.001) as predictors of TE-BR failure. Multivariate analysis confirmed NAC (HR 2.73, p=0.003) and acute RT toxicity (HR 3.16, p<0.001) as independent risk factors. Acute RT toxicity rates were similar between NAC and AC groups (p=0.604). Completing TE expansion before PMRT in NAC patients was linked to higher failure probability (HR 2.58, p=0.023).ConclusionOur study is the first to report TE-BR outcomes in women who undergo NAC versus AC in the context of PMRT. Our findings indicate inferior TE-BR outcomes following NAC when PMRT is delivered, emphasizing the importance of shared decision-making between patients and doctors about optimal surgical choice. If eligible, breast conservation or alternate BR technique should be strongly considered in the setting of NAC and future research should explore optimal reconstruction strategies.